Arab Modernists’ Positions on the Sunnah: Ḥasan Ḥanafī, Muḥammad Shaḥrūr, and Sayyid al-Qimnī - Alanazi, Asya (2023)
This study aims to analyse and evaluate the critical ideas of a group of selected Arab modernist thinkers researching and trying to apply new ways to re-read and interpret the Sunnah, and try to explain it by combining knowledge of Islamic traditions and knowledge of the achievements of Western modernity in their interpretation of canonical texts. The scope of this thesis relates to the ideas of the Egyptian leftist thinker and philosopher Ḥasan Ḥanafī (d. 2021), the Syrian Quranist thinker Muḥammad Shaḥrūr (d. 2019), and the Egyptian secular thinker Sayyid al-Qimnī (d. 2022). Ḥanafī seeks to reconstruct the traditions of Islam by adopting a critical historical mode of interpretation. His ideology represents a transmission of the French Enlightenment values of rationality and human consciousness to the Arab world; consequently, the Sunnah has no direct intrinsic significance for Ḥanafī, as it bears no import for his rationalist agenda. Thus, his treatment of it is mainly confined to reiterating Western orientalist critiques of the science of ḥadīth, which in his view demonstrate the lack of practical relevance of the Sunnah. This thesis assesses how Muḥammad Shaḥrūr understood the Prophet’s ḥadīth in his particular theoretical lens, which is based on Quranic rulings. In his contemporary reading of the Sunnah, he rejects its legislative authority, and limits the scope of regulation to a single source, namely the Qurʾān. Al-Qimnī’s position stems from his secular standpoint, which argues that the primary religious texts of the Qurʾān and Sunnah have no credibility as legitimate sources. By employing his socio-historical methodology, al-Qimnī attempts to secularize law in Arab societies, which is even further vindicated through his revisionist history of the entire Islamic tradition. Despite the ambitious nature of these Arab modernist thinkers’ claims that they offer a contemporary reading that suits the aspirations of modern Arab societies, the key argument of this thesis is that all three of the studied figures lack an accurate methodological application in their attempts to re-evaluate the Sunnah. The lack of solid methodological basis for their analyses is fundamentally problematic, and actually impinges on the integrity of their actual methods. Because there is no coherent demonstration of how their methods work in praxis, it is impossible for the academic analyst to discern any methodological demonstration that might be conducive to practical applications. Consequently, it is difficult to move beyond classical orientalist critiques of traditional Islam based on these thinkers, due to the incoherent framing of their offered modernist paradigms. A more robust and grounded academic approach, grounded within Islamic studies, can contribute to Arab reformist thought in all its analytical levels and dimensions using more diverse and coherent methodological paradigms and methods, including jurisprudence and ḥadīth-centred approaches to understand and interpret canonical texts in relation to contemporary intellectual currents, helping move forward civil discourse and socio-cultural development in Arab societies in addition to driving academic progress in Arab modernist philosophy.